Aplikasi Pemasaran Kue Tradisional Gorontalo Menerapkan User Centered Design: Aplikasi Pemasaran Kue Tradisional Gorontalo Menerapkan User Centered Desig - Fitriyanti Suleman; wati (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
The people of Gorontalo have a habit of consuming cake at breakfast and the tradition of providing cake at celebration events. However, the bustle of urban communities who do a lot of activities outside the home to work, thus making them prefer to buy cakes at cake sales places. Based on the current survey, traditional Gorontalo cakes are less exposed because more and more modern cakes are starting to enter the market, especially in cafes and restaurants, resulting in a decrease in the income of traditional cake traders. This study aims to help Gorontalo traditional cake traders to get digital sales media in order to face business competition in the current digital economy era. The application is designed based on a website by applying the User Centered Design method so that users in every stage of system development are also involved and the system formed can be used according to user needs. The application design uses the PHP programming language and data processing with MySQL DBMS. The system user interface is made simple so that the process of inputting and processing sales data and marketing transactions is more practical. User access on the system is made for administrators as system control and on the client side, access will be opened for traditional cake traders and community users as buyers or consumers. The results of system testing using blackbox testing are tested on the page views of all system users, namely the admin page, merchant page and buyer or community user page, the results of the blackbox test are obtained in accordance with the display design and system functions expected by system users.